Associations between weight perception and weight status with perceptions of the body positivity movement - Rupp, K.; McCoy, S.M. (American Journal of Health Promotion, 2024)
Purpose: To explore the relationships between weight status, weight perceptions, and perceptions of the body positivity movement on social media. Design: Cross-sectional. Setting: Online through the Qualtrics platform. Subjects: Participants (N = 521; mean 26.6 ± 5.1 years) were recruited using Qualtrics online panels. Measures: The study survey included questions about participant demographics, weight status, and weight perception. Subjects rated 6 study-specific viewpoint questions about the body positivity movement on a 5pt Likert scale. Analysis: Multinomial logistic regression models adjusted for relevant confounders assessed the associations between objective weight status, perceived weight status, and perceptions of the body positivity movement. Results: Objective weight status was not associated with perceptions of the body positivity movement. Perceptions of weight status were associated with perceptions of the body positivity movement in young women, with those that perceived themselves as overweight more likely (OR = 1.67, P < 0.05) to disagree with the statement that “the body positivity makes people less likely to lose weight.”. However, young women that perceived themselves as having a lower weight status were less likely (OR = 0.54, P < 0.05) to agree with the statement that “the body positivity movement empowered women” as well as “being inclusive of people of all sizes” (OR = 0.56, P < 0.05). Conclusion: Weight perception, rather than objective weight status, may be a stronger predictor of weight bias and views of the body positivity movement. © The Author(s) 2024.
Keywords: body image; body positivity movement; dept.hms; obesity; peer-reviewed; weight perception